Perspectives of Social System Crisis: Comparative Analysis - E. A. Gryzunova (Vestnik MGIMO-Universiteta)
The article deals with the development of perspectives of crisis and crisis management in sociology. The author describes the characteristics and the classifications of crisis events and their interconnection with the related terms. Recommendations of constructing a complex crisis management system are proposed.